A Self-Sovereign Identity-Based Authentication and Reputation Protocol for IoV Applications - Victor Emanuel Farias da Costa Borges; Alvaro Sobrinho; Danilo F. S. Santos; Angelo Perkusich (IEEE Access)
The Internet of Vehicles (IoV) ecosystem faces significant security challenges in authentication and reputation management, especially in scenarios lacking cellular coverage. In such environments, the lack of real-time identity verification and trust assessment increases the risk of false alerts, message injection, and cooperative system failures, potentially leading to advanced driver assistance systems malfunctions or traffic accidents. While the Cellular Vehicle-to-Everything (C-V2X) architecture provides robust security features under coverage, it lacks standardized mechanisms for decentralized authentication and trust evaluation when connectivity is unavailable. This paper introduces RepuAuth-IoV, a novel self-sovereign identity-based protocol that integrates decentralized authentication with a distributed reputation system tailored for IoV applications. RepuAuth-IoV empowers vehicles to autonomously manage identities and reputations using verifiable credentials, eliminating dependence on centralized authorities. Key innovations include a lightweight proof of reputation mechanism based on multi-party computation, enabling vehicles to collaboratively assess trustworthiness using recent spatiotemporal data without compromising privacy. To validate the protocol’s correctness and resilience, we formally modeled its behavior using hierarchical coloured Petri nets and verified critical properties through temporal logic model checking. Results demonstrate RepuAuth-IoV’s effectiveness in ensuring secure and privacy-preserving C-V2X communications, even in disconnected or adversarial environments. Compared to blockchain-based solutions, our protocol achieves similar security goals with significantly lower computational and communication overhead, offering a scalable and practical solution for real-time trust management in heterogeneous IoV deployments.